Kémek a porfészekben. Rimner Gábor története - Papp, Gábor Zsigmond (Hungary, 2009)
Aside from professional agents, the imperialist intelligence agencies commissioned secret agents from all walks of life. How were they contacted? What tasks were they assigned to? How did you quit spying?
Keywords: Documentary films